Determination of Nickel, Copper and Zinc in Water Samples After Cloud Point Extraction Using Ammonium O,O-Dicyclohexyldithiophosphate and Triton X-114 by Flame Atomic Absorption Spectrometry - Yagan Asci, Mehtap; Efendioglu, Aysegul; Bati, Bekir (Asian Journal of Chemistry, 2012)
A simple and practical cloud point extraction-preconcentration method for trace amounts of Ni, Cu and Zn by flame atomic absorption spectrophotometry was proposed. The laboratory madereagent ammonium O,O-dicyclohexyldithiophosphate which has not previously been used for analytical purpose and the nonionic surfactant Triton X-114 were used for cloud point extraction. The cloud point was formed in the presence of NaCl at 60 ºC. After phase separation, the surfactant-rich phase was diluted with ethanol acidified with 0.1 mol L-1 HNO3 and the final solution was determined by flame atomic absorption spectrometry. Under the optimal experimental conditions, calibration graphs were linear in the range of 20-120, 10-80 and 6-60 μg L-1, with detection limits of 1.41, 1.51 and 2.92 μg L-1 for Ni, Cu and Zn, respectively. The proposed method was applied to the determination of Ni, Cu and Zn in natural water samples and certified reference alloys. Results found were in good agreement with certified values.